Control Strategy for Distributed Integration of Photovoltaic and Battery Energy Storage System in Micro-Grids - Alias Khamis; Mohd Ruddin Ab. Ghani; Gan Chin Kim; Mohd Shahrieel Mohd Aras; Muhammad Aswad Bin Zabide; Tole Sutikno (Universitas Ahmad Dahlan, 2018)
The micro-grid deployments are growing with independently, power system designers, manufacturers and researchers for the applications where the loads are more efficient association with extra output sources such as Battery Energy Storage System (BESS), and Photovoltaic (PV) systems. Using renewable source as main sources for micro-grid system also can avoid from the pollution to occur. Energy storage when combined with PV system can provide a stronger economic performance, as well as an added benefit of backup power for critical loads. This project proposed control strategies for integration of BESS and PV in a micro-grid. The operation enables the maximum PV and BESS utilization during different operating condition of the micro-grid, grid connected, islanded mode or a process between these two operations. The project will focus on analyzing the performance between photovoltaic system and battery in the simulations of micro-grids system and validate the simulation result using MATLAB/SIMULINK software. After the simulation was analyzed, the understanding of benefit in using renewable energy source as main power supply with support from battery energy storage to supply the power to the loads and power managements is realized in the different modes on micro-grid which is grid connected or islanded states. When the power generation from PV system was not enough to accommodate electric loads, the BESS or from secondary side of transformer will supply the insufficient power.